Etika dan Moral dalam Bisnis Islam - Emalia Anggita; Cindy Adelia; Sindi Pratiwi; Nur Hasannah; Ropita Indah Siregar (Al-Sharf: Jurnal Ekonomi Islam, 2021)
Ethics is an important thing in everyday life, where ethics is the main foundation in social life. Ethics is also needed in the business world, the existence of ethics can develop the company that has been built. The reason is, in this era of development of the digital age, business development ethics are rarely used by the public, because they think it is a difficult thing or rules that have many complexities. In fact, if the company wants to achieve the goals of the company itself, then ethics is needed, to achieve a desired goal. This paper reveals or describes the importance of business ethics in the development of a company, where the method used is literature study. The results obtained, that ethics and morals are very important in the development of a company, both of which are closely related to the company's environment. The environment can make the company grow, because of the interaction between the company and the community.  Keywords: Ethics, Morals, Islamic Business